2018
DOI: 10.1007/s00167-018-4917-3
|View full text |Cite
|
Sign up to set email alerts
|

Good clinical and functional outcomes at mid-term following autologous osteochondral transplantation for osteochondral lesions of the talus

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 30 publications
2
59
0
4
Order By: Relevance
“…OAT was used to treat the patients with large subchondral cysts. A number of studies have reported good to excellent outcomes of MF and OAT at a mid-term follow-up [27][28][29][30][31][32]. Besides the management of intraarticular lesions, lateral ligaments reconstruction was performed for the patients combined with CAI.…”
Section: Discussionmentioning
confidence: 99%
“…OAT was used to treat the patients with large subchondral cysts. A number of studies have reported good to excellent outcomes of MF and OAT at a mid-term follow-up [27][28][29][30][31][32]. Besides the management of intraarticular lesions, lateral ligaments reconstruction was performed for the patients combined with CAI.…”
Section: Discussionmentioning
confidence: 99%
“…As lesões osteocondrais do tálus são lesões relativamente frequentes e a literatura tem orientado o seu tratamento dependendo do tamanho, profundidade e se a lesão é primária ou não. O auto-enxerto osteocondral é uma técnica de substituição indicada para lesões grandes, profundas e recorrentes (após falha de procedimentos reparatórios como estimulação da medula óssea) (1,6) .…”
Section: Discussionunclassified
“…Os resultados clínicos e radiológicos são homogeneamente bons na literatura (1) , porém falhas ocorrem em até 10% dos pacientes (4) .…”
Section: Discussionunclassified
See 2 more Smart Citations